Study on expert system for hitch diagnosis of electrically controlled automatic transmission based on vague inference - CHEN Kai-kao; ZHENG Wen-zhong; HE Yong (浙江大学学报. 农业与生命科学版)
Expert system for hitch diagnosis of electrically controlled automatic transmission, which is based on the combination of vague technology and multimedia technology, is presented. Then, vague inference is specially described with the help of vague comprehensive evaluation. On the usage in types of automatic transmission, the expert system shows a lot of merits, such as simple of inference process, unusual rapidity and high accuracy and so on.